2015
DOI: 10.4238/2015.december.23.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginkgo biloba extract on matrix metalloproteinase-3 expression in a rat model of chondrocyte injury

Abstract: ABSTRACT. A rat model with cartilage chondrocyte injury was established using interleukin-1β (IL-1β) to investigate the effect of Ginkgo biloba extract (EGb) on matrix metalloproteinase-3 (MMP-3) expression. Rat chondrocytes were extracted and randomly divided into six groups: control group, IL-1β (model) group, IL-1β + dexamethasone group, and IL-1β + EGb group (both high and low dose groups). Reverse transcriptase polymerase chain reaction and enzyme-linked immunosorbent assay were used to detect MMP-3 expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Previous studies had confirmed the treatment with Ginkgo Biloba significantly had decreased the mRNA and the level of Matrix Metallo Proteinase (MMP-2 and MMP-9) expressions [35]. GBE also expressively had lowered the production of MMP-3 through damage to the inflammatory chondrocyte [36]. Thus, MMP-3 inhibition may be a new mechanism of GBE for the treatment of VMC.…”
Section: Ginkgo Biloba With Mechanisms To Reduce the Microbial Infectmentioning
confidence: 86%
“…Previous studies had confirmed the treatment with Ginkgo Biloba significantly had decreased the mRNA and the level of Matrix Metallo Proteinase (MMP-2 and MMP-9) expressions [35]. GBE also expressively had lowered the production of MMP-3 through damage to the inflammatory chondrocyte [36]. Thus, MMP-3 inhibition may be a new mechanism of GBE for the treatment of VMC.…”
Section: Ginkgo Biloba With Mechanisms To Reduce the Microbial Infectmentioning
confidence: 86%
“…Previous study had proved Ginkgo biloba extract treatment significantly lowered the mRNA and protein expression levels of MMP‐2 and MMP‐9 . There was also evidence that Ginkgo biloba extract significantly reduced MMP‐3 production during inflammatory chondrocyte damage . Thus, the inhibition of MMP‐3 expression may be a potentially new mechanism of Ginkgo biloba extract for the treatment of VMC, which was confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the progression of OA, MMPs (including MMP-3 and MMP-13) are important regulators. MMP-3, as a matrix lysin, can decrease the expression of collagen and proteoglycans and activate other collagenases (37). MMP-13 is a collagenase that regulates matrix degradation and binds to type II collagen in the ECM (7,38).…”
Section: Discussionmentioning
confidence: 99%